Concept of “baku masuk” as a harmonious Cultural symbol in ambon - Nurlaila Tuanany (Balai Diklat Keagamaan Ambon, 2022)
This paper aims to describe how the dominant culture of the Ambonese can be used as a symbol of harmony in cultural plurality and ethnic pluralism in Ambon City. The cultural plurality that has been segregated through knowledge of territorial and geographical boundaries as a differentiator can be overcome through the